GROUNDWATER QUALITY IN TWO RURAL COMMUNITIES FROM CLUJ AND BISTRIȚA-NĂSĂUD COUNTIES – ROMANIA - ROȘU, Cristina; ROBA, Carmen; PIȘTEA, Ioana; BÂȘCOVAN, Bogdana; DEVIAN, Ovidiu (Studia Universitatis Babeș-Bolyai Ambientum, 2020)
In Romania, there are rural areas where the access to safe drinking water sources is still an unsolved issue. The main objective of the present study was to assess the quality of several underground drinking water sources from two rural communities from Romania and to evaluate the suitability of using those water sources in drinking and agricultural purposes. The investigated parameters were: pH, redox potential (Eh), electrical conductivity (EC), total dissolved solids (TDS), salinity, dissolved ions (F-, Cl-, Br-, NO2-, NO3-, PO4-3, SO4-2, Li+, Na+, NH4+, K+, Mg2+, Ca2+) and metals (Fe, Zn, Cr, Cu, Cd, Ni, Pb and Mn). The analyses indicated high levels of sulphates (up to 353.2 mg/l) in the wells from Cluj County and high concentrations of nitrates (up to 111.4 mg/l) and nitrites (up to 1.49 mg/l) in the wells from Bistrița-Năsăud County, these parameters frequently exceeded the safely limits imposed by national and international legislation. The levels of the other investigated parameters were generally below the maximum limits imposed by national and international legislation. Based on the sodium adsorption ratio, sodium percentage and magnesium adsorption ratio values, most of the investigated water sources can be safely used in agriculture purposes.